„Nasz elementarz” – krótki opis daru, który zubaża obdarowanych - Dorota Klus-Stańska (Problemy Wczesnej Edukacji)
The text is a critical analysis of the assumptions and content of “Nasz elementarz”, a textbook for the first grade of the primary school which has been promoted by the Ministry of Education. An overt attempt at the unification, control, and limiting of the development space of the youngest pupils has been indicated. Two theoretical perspectives have been adopted for the analysis: constructivism and the Foucauldian concept of normalizing discourse. The discourses underlying the textbook, which are permeated by relations of oppressive power over children, have been identified: the discourse of the child (infantile child discourse), of childhood (closed and colourless childhood discourse), and of knowledge (limited knowledge discourse).